Responses of potato root architecture and physiological indexes to drought stress at different growth stages - LI Jiaxin; ZHANG Tianci; REN Xiaoyue; LI Sixuan; CHEN Yanyun (Xibei zhiwu xuebao)
[Objective] The present study aimed to elucidate the response of the potato root system to drought stress at different developmental stages. Additionally, the study sought to identify the underlying mechanisms that confer drought resistance in potato root system. This study will provide a theoretical foundation for potato production under drought stress. [Methods] Using ‘Jizhang Potato No.12’ as the material, an indoor potting experimental design was adopted to study potato growth indexes, root conformation, and root physiological indexes at different reproductive periods under two treatments of severe drought [relative soil moisture content (45±5)%] and normal watering [relative soil moisture content (75 ±5)%]. [Results] The plant height, stem diameter, total root length, total root surface area, and total root volume of the potato were found to be significantly lower than those of the control throughout the reproductive period under drought stress. Single plant yield, number of potatoes per plant and starch content were significantly lower in the drought stressed group than the control, and reducing sugar was significantly higher in the drought stressed group than the control. The roots of potatoes subjected to drought stress exhibited heightened vigor, MDA, proline, and soluble sugar levels compared to the control, with these values increasing as the duration of drought prolonged. Additionally, the SOD and POD activity levels in these roots were higher than the control, with SOD displaying a delayed response during the early stages and POD activity demonstrating a rapid surge during the tuber formation phase. [Conclusion] The growth, development and yield of potatoes were found to be impeded by drought stress. The antioxidant enzyme system and osmoregulatory substances within the potato root system exhibited a rapid response to drought stress, enabling the plant to cope with the damage caused by drought stress and demonstrating a certain degree of drought resistance.